From the problematic situation to the scientific educational problem - Aguirre Chávez, Felipe (2016)
The scientific problems of educational research emerge from the knowledge of the current state of development of the subject to be investigated. The first stage is the diagnosis, the application of instruments, for exploratory purposes, such as interviews, surveys, observations, etc .; where the researcher, regardless of his object of study, unravels, establishes or determines problematic situations with his prospects for solution. Metaphorically speaking, every problematic situation comes with the formulation of the problem under the arm; But setting it up as a viable, novel and relevant scientific problem requires motivation and specific problematization skills in its multiple solution perspectives.  Depending on the focus and skills of the researcher, there are up to two basic possibilities: to successfully pass from the problematic situation to the formulation of the scientific problem or to be anchored in the dead end of the impossibility of problematizing; and, therefore, to lag the production of new knowledge.